Diretrizes curriculares para o ensino da Educação Física nos cursos técnicos integrados ao ensino médio do Instituto Federal do Espírito Santo - Abreu, Jose Roberto Goncalves de (2020)
This Thesis investigated a period of thirty years of the discipline of Physical Education in Technical Education Integrated to High School - ETIEM, having as reference, 21 campuses of the Federal Institute of Education of the State of Espírito Santo - Ife